Examining the Effect of Leadership Characteristics of Administrators on Creating School Culture (Journal of Management and Educational Sciences, 2025)
The purpose of this study is to examine the effects of school principal leadership on school culture. The study was conducted using a relational screening model. According to the study results; it is seen that the leadership styles and school culture perceptions of school principals are above average. In the examination conducted according to gender; the leadership perception of male school principals is higher than that of females. Again, the perception of male school culture is higher than that of females. In the examination conducted according to marital status; according to teachers' opinions, the leadership styles and school culture perceptions of school principals do not change according to married and single status. In the examination conducted according to age; according to teachers' opinions, the leadership styles and school culture perceptions of school principals do not change according to age groups. In the examination conducted according to years of service; according to teachers' opinions, the leadership styles and school culture perceptions of school principals do not change according to years of service groups. In the examination conducted according to school level; according to teachers' opinions, the leadership styles and school culture perceptions of school principals do not change according to schools at different levels. Finally, according to teachers' opinions, there is a high-level, significant and positive relationship between the leadership styles of school principals and school culture perceptions. In addition, the leadership styles of school principals significantly predict the total score perceptions of school culture. Accordingly, a 100-unit increase in the participants' democratic leadership sub-dimension increases school culture behavior by 49%. Again, a 100-unit increase in the participants' autocratic leadership sub-dimension increases school culture behavior by 19.1%.